If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/(c-6)=-5/2c+9
We move all terms to the left:
1/(c-6)-(-5/2c+9)=0
Domain of the equation: (c-6)!=0
We move all terms containing c to the left, all other terms to the right
c!=6
c∈R
Domain of the equation: 2c+9)!=0We get rid of parentheses
c∈R
1/(c-6)+5/2c-9=0
We calculate fractions
2c/(2c^2-12c)+(5c-30)/(2c^2-12c)-9=0
We multiply all the terms by the denominator
2c+(5c-30)-9*(2c^2-12c)=0
We multiply parentheses
-18c^2+2c+(5c-30)+108c=0
We get rid of parentheses
-18c^2+2c+5c+108c-30=0
We add all the numbers together, and all the variables
-18c^2+115c-30=0
a = -18; b = 115; c = -30;
Δ = b2-4ac
Δ = 1152-4·(-18)·(-30)
Δ = 11065
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$c_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$c_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$c_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(115)-\sqrt{11065}}{2*-18}=\frac{-115-\sqrt{11065}}{-36} $$c_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(115)+\sqrt{11065}}{2*-18}=\frac{-115+\sqrt{11065}}{-36} $
| 5x+3=x=-10 | | 18+19r=-18+17r | | 9-3x-5-3×=7 | | 12x+3x-2x=6+18-13x | | 18+19r=18+17r | | 1/2(c-6)=-5/2c+9 | | 3x+9x-5x-6=3x-6x+10 | | 2x+5+3x=-2x+9 | | 5x=38-4.9x^2 | | 3(x-1/2)=5(x+7/ | | 3x+9x-5x-6=6x=10 | | -8+9z=-7+8z-8 | | 10(r-86)=60 | | 2*t^2+3*t-10=0 | | X^2-2x-122=0 | | r-33/6=60 | | 5x-(x+1)=5-x | | 5x+3=x-0 | | 11x-9x=5+2x-3 | | 6(c+4)=90 | | 1.02x=1,5 | | 3(b-4)=-2b+8 | | 90=6(c+4) | | 4b-2=3b-4 | | 5z^2+5z=0 | | 2(11-4x=38 | | s-62/7=3 | | f/5+14=19 | | 3/5x-6=x | | 3+5|8-2x|=63 | | 6z+z=6z-9 | | 2u+2(80)=450 |